2022
DOI: 10.3390/genes13071247
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome and Interaction Protein Analysis Reveals the Mechanism of IbMPK3-Overexpressing Transgenic Sweet Potato Response to Low-Temperature Stress

Abstract: The sweet potato is very sensitive to low temperature. Our previous study revealed that IbMPK3-overexpressing transgenic sweet potato (M3) plants showed stronger low-temperature stress tolerance than wild-type plants (WT). However, the mechanism of M3 plants in response to low-temperature stress is unclear. To further analyze how IbMPK3 mediates low-temperature stress in sweet potato, WT and M3 plants were exposed to low-temperature stress for 2 h and 12 h for RNA-seq analysis, whereas normal conditions were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…The high degree of connectivity in the predicted PPI network suggests that these proteins regulate multiple developmental pathways in a highly coordinated manner. Several IbPYL, IbPP2C, and IbSnRK2 genes were differentially expressed in transgenic sweet potato plants that had stronger low-temperature stress tolerance than wild-type plants [59]. Solis et al [60] found an IbAREB gene was up-regulated during drought stress.…”
Section: Plos Onementioning
confidence: 99%
“…The high degree of connectivity in the predicted PPI network suggests that these proteins regulate multiple developmental pathways in a highly coordinated manner. Several IbPYL, IbPP2C, and IbSnRK2 genes were differentially expressed in transgenic sweet potato plants that had stronger low-temperature stress tolerance than wild-type plants [59]. Solis et al [60] found an IbAREB gene was up-regulated during drought stress.…”
Section: Plos Onementioning
confidence: 99%
“…Although sweet potato has the advantage of being drought tolerant after establishment, dry matter accumulation and root tuber enlargement are inhibited under drought stress, which seriously hampers production. This issue contains seven research papers focusing on sweet potato in response to the biotic [ 1 ] and abiotic stresses [ 2 , 3 , 4 , 5 , 6 , 7 ]. Genetic engineering methods can be used to improve drought tolerance.…”
mentioning
confidence: 99%